Bariatric surgery and health outcomes: An umbrella analysis - Liao, Jing; Yin, Yiqiong; Zhong, Jing; Chen, Yanjun; Chen, Yanbing; Wen, Yue; Cai, Zhaolun (Frontiers in Endocrinology, 2022)
Background: There is a relative lack of data that systematically investigates the breadth and validity of the association between bariatric surgery and health-related outcomes. We aimed to evaluate the quantity, validity, and credibility of evidence regarding the association between bariatric surgery and health-related outcomes using an umbrella review of meta-analyses. Methods: We systematically searched PubMed, Embase, and the Web of Science databases from inception until December 2, 2021, to identify meta-analyses of observational or interventional studies that investigated the association between bariatric surgery and multiple health outcomes. We extracted the summary effect size and 95% confidence interval (CI) data. The Assessment of Multiple Systematic Reviews (AMSTAR-2) and Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) guidelines were used for methodological and evidence quality assessments, respectively. Results: Twenty-eight studies with 82 different health-related outcomes were included in this umbrella review. Beneficial effects of bariatric surgery have been observed in cancer incidence, mortality, cardiovascular risk, polycystic ovary syndrome (PCOS), anxiety symptoms, depressive symptoms, gestational diabetes mellitus, gestational hypertension, large for gestational age (LGA), macrosomia, post-term birth, risk of kidney stones, albuminuria, urinary incontinence, fecal incontinence, Barrett's esophagus, and diabetic retinopathy. However, adverse effects of bariatric surgery were observed for maternal anemia, perinatal mortality, congenital anomalies, preterm birth, neonatal intensive care unit (NICU) admission, intrauterine growth restriction, small for gestational age (SGA), fracture risk, upper limb fracture, suicide, self-harm, and alcohol use disorder (AUD). Conclusions: Current evidence suggests that bariatric surgery improves the majority of health-related outcomes; however, caution is advised given it may increase the risk of adverse mental effects, perinatal problems, and fractures.